Case Report: Double Visualization Intubation Strategy for Patients With Ankylosing Spondylitis - Chen, Wei-can; Lin, Shu; He, He-fan (Frontiers in Medicine, 2022)
Background: Ankylosing spondylitis is an autoimmune disease involving the axial bone. Because it leads to rigidity of the spine and joints, especially when involving the cervical spine, it will cause a difficult airway, creating a major challenge for airway management. Herein, we report presents a double visual intubation strategy for severe ankylosing spondylitis patients who are difficult to intubate with a video laryngoscope. Case presentation: A 31-year-old patient with severe ankylosing spondylitis has a seriously restricted neck movement that makes it hard to insert a tracheal tube using only a video laryngoscope. With the aid of video laryngoscope, we then guided the endotracheal intubation using a lighted stylet. Eventually, the oropharynx was opened sufficiently so that the tracheal tube could be rapidly introduced below the epiglottis and entered the glottis. Conclusion: In conclusion, the video laryngoscope is a viable operation to assist lighted stylet guided endotracheal intubation in severe ankylosing spondylitis patients after video laryngoscope intubation failure.